+0  
 
0
305
1
avatar

Choose the correct answer choice.

 Nov 12, 2018

Best Answer 

 #1
avatar+342 
0

Generally its: 

\(sin^2θ + cos^2θ=1 \)

so \(cosθ=\sqrt{1 - sin^2θ }=\sqrt{1 - \frac{4}{25} }=\sqrt{\frac{25}{25}-\frac{4}{25}}=\sqrt{\frac{21}{25}}=\frac{\sqrt{21}}{5}\)

.
 Nov 12, 2018
 #1
avatar+342 
0
Best Answer

Generally its: 

\(sin^2θ + cos^2θ=1 \)

so \(cosθ=\sqrt{1 - sin^2θ }=\sqrt{1 - \frac{4}{25} }=\sqrt{\frac{25}{25}-\frac{4}{25}}=\sqrt{\frac{21}{25}}=\frac{\sqrt{21}}{5}\)

Dimitristhym Nov 12, 2018

20 Online Users

avatar